Abuse of Dominance Under Article 102 TFEU And Data Protection Within the Context of Bundeskartellamt’s Facebook Investigation - Toivanen, Tuuli (fi=Turun yliopisto|en=University of Turku|, 2017)
This paper explores whether data protection infringement could be found a key parameter in determining an abuse of a dominant position under the Article 102 of the Treaty on the Functioning of the European Union. The theme has been inspired by German competition authority Bundeskartellamt’s investigation on, whether Facebook has abused its dominant position by infringing data protection. The study is legal dogmatic and it discusses data’s and data protection’s interaction with competition law in the context of online platforms. Attention is especially paid to the question on, infringing which features of data protection could be seen as abuse of dominance on online platforms and which forms of abuse could be identified. According to the study it appears that especially the validity of data subject’s consent to wide-ranging data processing rights could be interpreted as exploitative abuse of unfair contractual term or a breach of dominant company’s special responsibilities. Another possible link may be seen between data protection regime’s principles of purpose limitation and data minimization and competition law regime’s exploitative abuse as excessive collection of data. However, there is no case law directly supporting either of these arguments.